Predictors of Outcome in Angiotensin Converting‐Enzyme Inhibitor‐Induced Angioedema. (2nd September 2014) - Kieu, Monica C. Q.; Rajasakher, Arun; Bangiyev, John N.; Thottam, Prasad J.; Wilburn, John; Stern, Noah; Levy, Phillip
Abstract : Objectives: (1) Identify high‐risk symptoms and anatomical regions involved in Angiotensin Converting‐Enzyme Inhibitor‐Induced Angioedema (AIIA) that may affect admission and placement, hospital length of stay, need for airway intervention, and clinical improvement versus deterioration. (2) Describe a clinical algorithm for the management and treatment of AIIA that would dictate placement of patients (ICU, general medical floor, observation unit, or discharge home), medical therapy, and the need for airway intervention (intubation or tracheostomy). Methods: A retrospective chart review of adult patients presenting to the emergency department (ED) at Detroit Medical Center diagnosed with AIIA from July 2010 to July 2013. Patients were followed from initial presentation until discharge. Descriptive statistics (frequency, means, and standard deviations) were calculated for all predictor, outcome, and control variables. Results: A total of 302 patients who were diagnosed with AIIA in the ED were evaluated with flexible laryngoscopy by an otolaryngologist. A total of 94% of patients were African American, with a slight female predominance of 63%. The most frequent presenting sign was lip swelling (62%). Angioedema confined to the lips was a negative predictor for airway intervention ( P <. 01). Also, patients with isolated lip swelling were less likely to have progression of symptoms ( P <. 05), and were less likely to require ICU monitoring ( P <. 05). Conclusion: This is the largest patient series to date of AIIA. Using the information from this study, a clinical algorithm was developed that details management of AIIA based on presenting signs and anatomic location, with otolaryngologists playing a vital role in the decision making process.